Symbols and Objects of Desire: The Ottoman Fashion Between Representation of the Turk and Manifestation of Power in the Italian Renaissance Peninsula - Eros Calcara (Religions)
The 16th century in Italy was an era of great cultural ferment, characterized by an intense exchange of ideas, goods and influences between the various European powers and the neighboring Eastern Empires, including the Ottoman Empire. Despite the climate of hostility, the “metus hostilis” towards the Turks, and the conflicts with the latter, during the 16th century, an obsession with what came from the East further developed. This article aims to explore the role of Ottoman fashion and style in the Italian Peninsula during this period, analyzing the artistic, cultural, and social influences that shaped Renaissance aesthetics and taste for these “status symbols”.